Food and society in classical antiquity - Garnsey, Peter (Key themes in ancient history., 1999)
This is a general study of food in antiquity. The book deals with food as food or nutrition. It also treats the non-food uses of food, focusing on the role of food in forming and marking the social hierarchy. Food defines the group, whether social, religious, philosophical or political.